2023
DOI: 10.1371/journal.pone.0283278
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base and metabolic parameters and cerebral oxygenation during the immediate transition after birth—A two-center observational study

Abstract: Objective The association between blood glucose level and cerebral oxygenation (cerebral regional oxygen saturation [crSO2] and cerebral fractional tissue oxygen extraction [FTOE]) in neonates has already been described. Aim of the present study was to investigate if acid-base and other metabolic parameters have an impact on cerebral oxygenation immediately after birth in preterm and term neonates. Study design Post-hoc analyses of secondary outcome parameters of two prospective observational studies were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…The correlations in the present study were observed despite the fairly narrow lactate range within the study population with values <2.9 mmol/L. Similar findings with negative correlations between lactate levels obtained from capillary blood and crSO 2 and with positive correlations between lactate levels and cFTOE in preterm neonates 15 min after birth were published by Mattersberger et al ( 20 ) as well as by Janaillac et al ( 21 ) in extremely preterm infants in the first 72 h after birth. The observed correlations could be explained by the fact that lactic acidemia induces pulmonary vasoconstriction and decreases cardiac stroke volume as a result of impaired cardiac contractility ( 22 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlations in the present study were observed despite the fairly narrow lactate range within the study population with values <2.9 mmol/L. Similar findings with negative correlations between lactate levels obtained from capillary blood and crSO 2 and with positive correlations between lactate levels and cFTOE in preterm neonates 15 min after birth were published by Mattersberger et al ( 20 ) as well as by Janaillac et al ( 21 ) in extremely preterm infants in the first 72 h after birth. The observed correlations could be explained by the fact that lactic acidemia induces pulmonary vasoconstriction and decreases cardiac stroke volume as a result of impaired cardiac contractility ( 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…BE is used for quantification of changes in metabolic acid-base status and together with umbilical artery pH it is crucial to estimate the risk for newborn cerebral damage (40,41). Mattersberger et al (20) indicated positive correlations between HCO 3 measured 15 min postnatally and cFTOE in term neonates and correlations of lower pH and BE also measured 15 min postnatally with lower crSO 2 and higher cFTOE in preterm neonates. A point of innovation of the present study compared to Mattersberger et al is the fact that by using umbilical cord blood the blood sampling is immediately after birth and might help to predict changes in the transition period and especially predict cerebral oxygenation in this vulnerable period (42).…”
Section: Discussionmentioning
confidence: 99%